Pengaruh Motivasi dan Kepuasan Kerja terhadap Stres Kerja Karyawan PT. PLN (Persero) Pembangkitan Selama Masa Pademi Covid – 19 - Sella Novia; Abdul Haris; Nefi Darmayanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to see the effect of work motivation and job satisfaction on job stress of employees of PT. PLN (Persero) generation during the covid-19 pandemic. The research subjects were 111 people with the sampling technique using total sampling. Data were collected using a Likert scale consisting of three scales, namely the work motivation scale, job satisfaction scale, and work stress scale. Data analysis technique using multiple regression analysis. The results obtained that there is a significant influence between work motivation and job satisfaction on work stress of employees of PT. PLN (Persero) generation during the covid-19 pandemic. The magnitude of the influence of motivation and job satisfaction on the work stress of employees of PT. PLN (Persero) generation during the covid-19 pandemic was 41.9% while the remaining 58.1% was influenced by other factors outside the study. From the results of the study, it was concluded that there was an effect of motivation and job satisfaction on employee job stress.